Byzantine Theoretical Treatises on Music in comparison with the Theoretikon Mega tes Mousikes by Chrysanthos of Madytos - Wolfram, Gerda (Epistēmēs Metron Logos, 2021)
Studying the Theoretikon Mega tes Mousikes one can state, that the ambition of Chrysanthos of Madytos was to preserve the old Byzantine tradition to a certain extent, but also to take into account the development of liturgical music during the last three hundred years. With the alterations in liturgical chant, music theory had to be revised and refounded on a new basis. (...)